Clinical and pathological evaluation of histopathological subtypes in patients with non-Hodgkin’s lymphoma - Tabakan, Feray; Nayir, Erdinc; Arican, Ali (The European Research Journal, 2016)
Objectives. Non-Hodgkin Lymphomas (NHLs) are tumours of the lymphoid system which originate from lymph nodes or extranodal lymphatic tissue. Since they represent a heterogeneous group of diseases, it is very important to determine prognostic factors apart from staging and identification of the patients with poor prognosis. The objective of our study is to investigate clinical characteristics, treatments applied, and their outcomes, survival rates, and prognostic factors which may be effective on survival.Methods. Clinical characteristics, treatments applied, and their outcomes, survivals, and prognostic factors which may be effective on the survival in 230 patients who were diagnosed as NHL, and consulted to our center between the years 2002, and 2015 were retrospectively evaluated.Results. Median age of our patients (male, 54.8 %, and female, 45.2 %) was 57 years. The most frequently seen histopathological subtype was diffuse large β cell lymphoma. We have seen that IPI score, β symptom, levels of LDH, albumin, β2 microglobulin, and lymphocyte counts are significant prognostic factors. Stomach was the most frequently involved extranodal organ. Advanced stage, higher IPI score, extranodal organ involvement were found to be correlated with shorter survival times.Conclusion. Everyday developments occur in the diagnosis, classification, and treatment of NHL. Therefore, it is important for medical centres to evaluate their treatment outcomes, and prognostic factors affecting their survival rates.